TECHNOLOGICAL SPECIFIC FEATURES ON FORMATION OF PLASMA POWDER COATINGS FROM CERAMICS WITH NON-EQUILIBRIUM STRUCTURE - V. A. Okovity; F. I. Panteleenko; V. M. Astashinsky; V. V. Okovity (Наука и техника)
The paper presents investigations on studying the influence of plasma jet parameters (current, sputtering distance, consumption of nitrogen plasma forming gas), fractional composition of an initial powder on characteristics of plasma powder coatings from ceramics with a non-equilibrium structure. Optimization of APS parameters (plasma spraying in air) has been carried out for the following materials: NiAl, Al2O3–Cr2O–TiO2 – 15 % (CaF2–Ni) and FeCr30Mo3 – 12 % CaF2 – 50 % TiC. The optimization of sputtering parameters has been made on the basis of obtaining maximum coefficient of the material use. Structure of coatings, their chemical and phase compositions have a determining effect on physical and mechanical properties of the coatings, in particular, on porosity, adhesion strength and wear resistance. In its turn, a structure and a composition of the coating formed on the substrate depend on energy characteristics of the plasma sputtering process, an efficiency of heat exchange processes between dispersed and gas phases of high-temperature plasma jet, and also on a composition, a structure, and properties of the used materials. Thus, a stable distribution of a solid oxide phase has been observed in the volumes of sputtered materials and there are no surface zones with a deficiency of such inclusions that positively affects operability of the investigated wear-resistant coatings. While carrying out plasma deposition of Al2O3–Cr2O–TiO2 – 15 % (CaF2-Ni) powders, a coating with a higher micro-hardness has been formed in comparison with Al2O3–Cr2O–TiO2 – 15 % (MoS2–Ni) powders that is due to a decrease in porosity and an increase in uniformity of coatings. Graininess of the coatings exerts a significant influence on density of coatings, nature of phase distribution and strength characteristics (wear resistance and adhesion strength).